Treatment and control of cure - Mendes, Rinaldo Poncio [UNESP]; Negroni, Ricardo; Arechavala, Alicia (Taylor & Francis, 2018)
The treatment of paracoccidioidomycosis should include general measures and a fight against the malnutrition-immunologic depression-infection triad, since malnutrition impairs the immune response and favors the installation of infectious diseases, including mycoses. The association of a sulfonamide derivative with trimethoprim has proved to be very effective in the initial treatment of paracoccidioidomycosis. The general measures include rest, treatment of associated diseases, among which verminosis is the most frequent, and control of aggravating conditions. A marked advance in the treatment of paracoccidioidomycosis has been made with the use of azole compounds. The criteria for cure of paracoccidioidomycosis are based on clinical, mycological, radiological and immunological data. Patients who are to receive the initial treatment should be submitted to close surveillance. A patient’s course during treatment depends on the severity of the clinical picture as well as on the therapeutic procedures.